2015
DOI: 10.1016/j.drugalcdep.2015.08.028
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported use of novel psychoactive substances in a US nationally representative survey: Prevalence, correlates, and a call for new survey methods to prevent underreporting

Abstract: Background In recent years, there has been an increase in emergence and use of novel psychoactive substances (NPS) in the US and worldwide. However, there is little published epidemiological survey data estimating the prevalence of use in the US. Method Data on self-reported NPS use came from the National Survey of Drug Use and Health (2009–2013), a national representative sample of non-institutionalized individuals in the US. Subjects were asked to provide names of (non-traditional) drugs they used that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
86
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 148 publications
(93 citation statements)
references
References 29 publications
4
86
2
Order By: Relevance
“…The proportion of past-year use of marijuana, LSD, ketamine, and/or DMT/AMT/Foxy increased, with greatest relative increases in DMT/AMT/Foxy use (i.e., 314%) from 2007/08 to 2013/14. Another study found that eight out of ten individuals who reported DMT/AMT/Foxy use or other tryptamines in the NSDUH also reported lifetime ecstasy use (Palamar et al, 2015). This increase in use of tryptamines may be due to a recent increase in popularity of DMT (Winstock et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of past-year use of marijuana, LSD, ketamine, and/or DMT/AMT/Foxy increased, with greatest relative increases in DMT/AMT/Foxy use (i.e., 314%) from 2007/08 to 2013/14. Another study found that eight out of ten individuals who reported DMT/AMT/Foxy use or other tryptamines in the NSDUH also reported lifetime ecstasy use (Palamar et al, 2015). This increase in use of tryptamines may be due to a recent increase in popularity of DMT (Winstock et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Both classic tryptamine psychedelics such as N,N-dimethyltryptamine (DMT) but also synthetic tryptamine-based "research chemicals" have been popular. [5,6]. N,N-Diallyltryptamine (DALT) derivatives represent an important group with 5-methoxy-DALT (5-MeO-DALT) being the most often reported example [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…N,N-Diallyltryptamine (DALT) derivatives represent an important group with 5-methoxy-DALT (5-MeO-DALT) being the most often reported example [7][8][9]. As such drugs may become controlled the creation of new substances with similar chemical structures and effects is aimed at circumventing legislative restrictions [5], which leads to significant challenges for drug testing laboratories in the attempt to be kept up-to-date with analytical methods and reference data [10,11]. One prerequisite is the knowledge of the NPS metabolism particularly for urine drug testing.…”
Section: Introductionmentioning
confidence: 99%
“…The use of these substances is vanishingly rare in general population studies (Champion, Teesson, & Newton, 2015;Martinotti et al, 2015;Palamar, Martins, Su, & Ompad, 2015) and thus knowledge of consumption patterns is scarce. According to the Flash Eurobarometer 401 (European Commission, 2014), nearly two-thirds of participants that had used a NPS within the past 12 months had used it in the context of parties.…”
mentioning
confidence: 99%